1997
DOI: 10.1007/bf02815177
|View full text |Cite
|
Sign up to set email alerts
|

Area-dependent CNS membrane response of muscarinic receptor to convulsant 3-mercaptopropionic acid

Abstract: It has already been shown that the administration of convulsant 3-mercaptopropionic acid at 150 mg/kg enhances binding affinity of muscarinic antagonist [3H]quinuclidinyl benzilate ([3H]QNB) to certain rat CNS membranes without affecting site number. Herein we employed a 100 mg/kg dose and tested [3H]QNB binding to cerebellar, hippocampal, and striatal membranes obtained from rats killed at preseizure, seizure, and postseizure stages. In cerebellum, binding increased 24, 65, and 19% a1 preseizure, seizure, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Present findings showed increased [ 3 H]QNB binding to CNS membranes preceding seizure onset and indicate the ability of cerebellum and hippocampus to respond promptly to convulsant MP, so that a direct effect of the drug on these areas may be postulated and changes cannot be attributed to seizures but rather seem to indicate a major role in seizure triggering. In support, we found significant changes in [ 3 H]QNB binding to hippocampal membranes after MP doses of 100 mg/kg (8) or 50 mg/kg (present findings). How-ever, no plausible explanation is available for the lack of effect of a higher MP dose (150 mg/kg) on binding to hippocampal membranes (7).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Present findings showed increased [ 3 H]QNB binding to CNS membranes preceding seizure onset and indicate the ability of cerebellum and hippocampus to respond promptly to convulsant MP, so that a direct effect of the drug on these areas may be postulated and changes cannot be attributed to seizures but rather seem to indicate a major role in seizure triggering. In support, we found significant changes in [ 3 H]QNB binding to hippocampal membranes after MP doses of 100 mg/kg (8) or 50 mg/kg (present findings). How-ever, no plausible explanation is available for the lack of effect of a higher MP dose (150 mg/kg) on binding to hippocampal membranes (7).…”
Section: Discussionsupporting
confidence: 89%
“…More recently, we have observed that a 100 mg/kg MP dose is able to enhance [ 3 H]QNB binding to CNS membranes following a similar pattern for cerebellum and hippocampus, which featured a rapid increase in binding with a trend to reversibility. At variance, changes in striatum appear later and seem more persistent, supporting that MP effect is area-specific (8).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Previous work from this laboratory has shown that convulsant MP modifies GABA system by decreasing GAD activity and GABA levels as well as alterating of cerebellar Purkinje cell morphology [ 8 , 9 ]. With a convulsant MP dose, [ 3 H]-QNB binding to muscarinic receptors is enhanced in CNS, an effect due to an increase in affinity without changes in binding site number [ 10 , 11 ]. However, a subconvulsant MP dose fails to induce any change [ 10 - 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since saline administration produces no change in any of the areas studied [ 11 ], uninjected rats were used as controls.…”
Section: Methodsmentioning
confidence: 99%